PENGARUH EFEKTIFITAS PEMBELAJARAN AQIDAH AKHLAK TERHADAP KEPRIBADIAN SISWA - FUAD (AZKIA : Jurnal Aktualisasi Pendidikan Islam, 2020)
The nature of students learning the subject of aqeedah morals is to instill morality in the personality of each individual in the process of teaching and learning in particular and in everyday life in general, then the aim of teaching aqeedah morals to students in Madrasas is solely to improve the devotion of children in particular and in daily life in general. educate God Almighty and have noble character in his life, both with the teacher and the community in their daily lives, Effectiveness is an effort made by the teacher in the teaching and learning process. Learning Should be with the effectiveness of moral aqidah learning will affect student personality towards better learning and teaching processes. Efforts to effectiveness the learning of moral aqidah is something that must be carried out by the teacher without exception. But what has happened so far is that not all teachers make effective the learning of aqidah morals in learning. Should be able to change the personality of students towards better learning, then all teachers must implement the effectiveness of learning aqidah morals to students